Phase and Microstructure Evolution in V-Ti-(Cr/W) Alloys. (2016) - Ghosh, Chanchal; Basu, Joysurya; R., Divakar; Mohandas, E.
Abstract: V-Ti-Cr alloys are the potential candidates for advanced high temperature structural applications, alternative energy research and improved hydrogen storage capacity. In the present work, Miedema model has been used to predict the phase stability of V-Ti-Cr/W systems. Alloys of selected compositions were prepared by arc melting the highly pure V, Ti and Cr. Microstructural and microchemical characterizations were carried out on two selected alloy compositions, one nearby the Ti-Cr rich side of the ternary enthalpy-composition diagram and the other from the binary V-Ti alloy. TEM characterizations confirmed the phase evolution in these two alloys as predicted by Miedema's model.